Switzerland - Dahinden, Janine (My University, 2015)
The multiethnic and multilinguistic character of Switzerland has represented a puzzle for major scholars on European nationalism since the nineteenth century. Research shows that this multiethnicity is a pivotal element of pride and central to the common Swiss imaginary of a “nation of will,” which embraces local, cantonal, and linguistic identities. In parallel, this particular case of collective nation building created strong and exclusive boundaries against immigrants and foreigners along national lines, thus ethnicizing and culturalizing immigrant policies and the naturalization regime.
Keywords: citizenship; ethnicity; migration; minorities; nationalism